Negotiated Obedience of Generation Z in Life Partner Selection: A Phenomenological Study in Islamic Family Law - Firstyadi, Sherly Oktavia; Kumaini, Ruston; Azzam, Muhammad (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2026)
This study provides an in-depth examination of the sociological and religious dynamics that emerge between individual autonomy and parental blessing in the process of choosing a life partner, particularly among Muslim Generation Z women. In the modern era, Generation Z is characterized by a strong appreciation for freedom, critical thinking, and personal autonomy, traits that frequently intersect with collective values and family traditions. Therefore, this study aims to comprehensively review these dynamics through the lens and perspective of Islamic law. To analyze this phenomenon, the study employs a qualitative approach using a phenomenological method, focusing specifically on how informants interpret their subjective life experiences. Data was collected through in-depth interviews with individuals who demographically fall into the Generation Z category. The findings indicate that autonomy is understood as a form of personal responsibility in shaping one's future, while parental blessing is essentially interpreted as a manifestation of prayer, a source of spiritual blessing, and a concrete implementation of the value of birrul walidain (devotion to parents) in religious practice. Despite differences in experiences and perspectives among the informants, they generally strive to strike a balance between personal desires and respect for their parents. From the perspective of Islamic law, an individual's right to choose a partner is recognized, provided it does not contradict sharia principles and proper conduct (adab) toward parents. The study concludes that a middle ground between individual autonomy and parental blessing can be achieved through open communication, mutual understanding, and spiritual approaches such as general supplication (do'a) and the prayer for guidance (shalat istikharah). These findings contribute to a better understanding of the relational dynamics between parents and children in the modern era, specifically within the context of Muslim Generation Z women.